Prognostic significance of lymphocyte monocyte ratio in patients with ovarian cancer. Issue 14 (April 2020) - Cai, Linrui; Song, Yanlin; Zhao, Xia
Abstract: Background: This study aimed to systematically assess the prognostic value of lymphocyte monocyte ratio (LMR) in patients with ovarian cancer through performing a meta-analysis. Methods: Web of Science, PubMed, EMBASE, Cochrane Library, and China National Knowledge Infrastructure databases were searched for potentially eligible studies. The baseline characteristics and relevant data were extracted. Hazard ratios with 95% confidence intervals (CIs) were combined to assess the prognostic value of LMR in patients with ovarian cancer. Results: Nine studies enrolling 2809 patients were included. The pooled hazard ratios of lower LMR for overall survival and progression free survival in patients with ovarian cancer were 1.71 (95% CI, 1.40–2.09) and 1.68 (95% CI, 1.49–1.88), respectively. Subgroup analysis and sensitivity analysis were also performed. No significant publication bias was found. Conclusion: Our results suggested that lower LMR was associated with poorer overall survival and progression free survival in patients with ovarian cancer. The findings may assist prognosis evaluation and future research on therapies based on modulating host immune response in ovarian cancer.